Immunogenicity and protective efficacy of adenoviral and subunit RSV vaccines based on stabilized prefusion F protein in pre-clinical models. Issue 6 (7th February 2022) - Saeland, Eirikur; van der Fits, Leslie; Bolder, Renske; Heemskerk-van der Meer, Marjolein; Drijver, Joke; van Polanen, Yolinda; Vaneman, Cornelis; Tettero, Lisanne; Serroyen, Jan; Schuitemaker, Hanneke; Callendret, Benoit; Langedijk, Johannes P.M.; et al.
Abstract: Respiratory Syncytial Virus (RSV) remains a leading cause of severe respiratory disease for which no licensed vaccine is available. We have previously described the derivation of an RSV Fusion protein (F) stabilized in its prefusion conformation (preF) as vaccine immunogen and demonstrated superior immunogenicity in naive mice of preF versus wild type RSV F protein, both as protein and when expressed from an Ad26 vaccine vector. Here we address the question if there are qualitative differences between the two vaccine platforms for induction of protective immunity. In naïve mice, both Ad26.RSV.preF and preF protein induced humoral responses, whereas cellular responses were only elicited by Ad26.RSV.preF. In RSV pre-exposed mice, a single dose of either vaccine induced cellular responses and strong humoral responses. Ad26-induced RSV-specific cellular immune responses were detected systemically and locally in the lungs. Both vaccines showed protective efficacy in the cotton rat model, but Ad26.RSV.preF conferred protection at lower virus neutralizing titers in comparison to RSV preF protein. Factors that may contribute to the protective capacity of Ad26.RSV.preF elicited immunity are the induced IgG2a antibodies that are able to engage Fcγ receptors mediating Antibody Dependent Cellular Cytotoxicity (ADCC), and the induction of systemic and lung resident RSV specific CD8 + T cells. These data demonstrate qualitative improvement of immune responses elicited by an adenoviral vector based vaccine encoding the RSV preF antigen compared to the subunit vaccine in small animal models which may inform RSV vaccine development.